Contributions of the rights approach to teacher training: a case study with teachers graduated from the University of Costa Rica - Naranjo Segura, Juan Carlos (2022)
The objective of this article is an analysis of the contributions that the human rights approach provides in the training of teachers and, therefore, an assessment of its importance and contribution in the exercise of the profession. It attends to a theoretical approach from three central axes: human rights, education in rights and the teaching role from said approach. To develop the research, a qualitative methodology was used, through which the experiences, the conceptual mastery and the points of view of practicing teachers, graduated from the University of Costa Rica and who took the course entitled " The Teaching of International Understanding and Human Rights”. Data collection was carried out through a semi-structured interview with three primary school teachers who are practicing their profession, and a qualitative questionnaire with open questions applied to fifteen teachers with the aforementioned characteristics. Among the main results is the visualization of the rights approach as a theoretical tool that allows the understanding of the context itself in relation to how respect for human rights is developed, this allows the development of skills such as critical thinking, analysis of social reality and active participation in society. In addition, it poses the teaching task as beyond a transmitter of content, positioning itself as an agent of social transformation.